Design of a dual-antenna and dual-band GPS receiver for CubeSats - Rodríguez, Santiago (2017)
During the last few years, there has been a rise in the use of nanosatellites because they offer a low cost and short development time alternative to larger satellites intended for longduration missions. The use of commercial components (COTS) instead of the expensive space-grade components required for long missions is one of the main reasons of the popularity of the nanosatellites. This paper presents the hardware design of a GPS receiver compatible with the CubeSat standard. The receiver has two antenna inputs and is capable of operating on the L1 and L2 bands. Since the proposed design is based on non-space qualified components, a tolerance and fault mitigation scheme for SEU and SEL events produced by the effect of radiation is implemented.